Therapeutic implications of altered cholesterol homeostasis mediated by loss of CYP46A1 in human glioblastoma - Mingzhi Han; Shuai Wang; Ning Yang; Xu Wang; Wenbo Zhao; Halala Sdik Saed; Thomas Daubon; Bin Huang; Anjing Chen; Gang Li; Hrvoje Miletic; Frits Thorsen; et al. (EMBO Molecular Medicine)
Abstract Dysregulated cholesterol metabolism is a hallmark of many cancers, including glioblastoma (GBM), but its role in disease progression is not well understood. Here, we identified cholesterol 24‐hydroxylase (CYP46A1), a brain‐specific enzyme responsible for the elimination of cholesterol through the conversion of cholesterol into 24(S)‐hydroxycholesterol (24OHC), as one of the most dramatically dysregulated cholesterol metabolism genes in GBM. CYP46A1 was significantly decreased in GBM samples compared with normal brain tissue. A reduction in CYP46A1 expression was associated with increasing tumour grade and poor prognosis in human gliomas. Ectopic expression of CYP46A1 suppressed cell proliferation and in vivo tumour growth by increasing 24OHC levels. RNA‐seq revealed that treatment of GBM cells with 24OHC suppressed tumour growth through regulation of LXR and SREBP signalling. Efavirenz, an activator of CYP46A1 that is known to penetrate the blood–brain barrier, inhibited GBM growth in vivo. Our findings demonstrate that CYP46A1 is a critical regulator of cellular cholesterol in GBM and that the CYP46A1/24OHC axis is a potential therapeutic target.